Rising trend of substance abuse in Pakistan: a study of sociodemographic profiles of patients admitted to rehabilitation centres. (February 2019) - Ghazal, P.
Abstract: Objectives: In Pakistan, the prevalence of drug addiction is increasing at an alarming rate. However, the risk factors, which are increasing vulnerability towards addiction, remain largely elusive. The major objective of this investigation was to study the sociodemographic variables common in addicted patients in order to identify vulnerable cohorts and risk factors, which increase predisposition towards substance abuse. Study design: This is a multi-site cross-sectional survey-based study. Methods: In this study, 102 male addicted patients admitted to drug rehabilitation centres of the Islamabad/Rawalpindi and fulfilling Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, criteria for dependence, were interviewed with the help of a structured questionnaire. Results: A total of 102 male patients participated in the survey. Participants mean age was 28.4 years (±9.8), whereas 14% were aged between 15 and 20 years. A large number of respondents (35%) initiated drug abuse in the teenage years. Majority of the subjects were skilled (60%) and had secondary education (47%), whereas 8% of the patients were students. Heroin was the most abused substance (48%) followed by cannabis (28%). The mean duration of substance abuse was between 1 and 5 years, whereas a significant fraction of subjects (8%) had more than 16 years of duration of abuse. Family disputes and peer pressure were the most common reasons for initiation of substance abuse. A significant fraction of patients (46%) reported to suffer from comorbid depression. Conclusions: The growing trend of abuse in highly addictive substances such as heroin in teenagers and in the skilled and educated stratum of society is of great concern and demands immediate preventive measures from the policymakers. Highlights: Drug abuse is increasing at an alarming rate in adolescents. Opioids abuse, specifically heroin, followed by cannabis, is on the rise among skilled and educated cohorts. Patients admitted to deaddiction centres are most likely to relapse due to the occurrence of comorbid depression.